IKLIM KOMUNIKASI ORGANISASI DAN KEPUASAN KOMUNIKASI PADA ORGANISASI SIPIL YANG BERNUANSA KEPOLISIAN (Studi Kasus Di PT. Asuransi Bhakti Bhayangkara) - TABRANI - SJAFRIZAL; Aminudin Junaedi (Universitas Bina Sarana Informatika, 2020)
Abstract - This study aims to determine how much the relationship between organizational communication climate and communication satisfaction at PT. Asuransi Bhakti Bhayangkara. The definition of a civil society organization is the police, namely the application of a command communication pattern that has become accustomed to being applied among security forces, and then also applied at PT. Asuransi Bhakti Bhayangkara. Even though PT. Insurance Bhakti Bhayangkara itself is one of the private companies (civil), so the right communication to use is a communication pattern that is supposed to be for civilians, not a command communication pattern, because the command communication pattern is more appropriate for security forces. In this command communication pattern, the communication flow tends to be dominated in the form of vertical communication, namely communication from top to bottom (Top Down Communication), when compared with from the bottom up (Up Down Communication). As one example of this command communication pattern, if the leader gives instructions to his subordinates, his subordinates must respond by saying